Anatomical features of inferior mesenteric and left colic arteries and surgery in colorectal cancer patients with persistent descending mesocolon. Issue 7 (12th April 2022) - Nozawa, Hiroaki; Okamoto, Kazuaki; Kawai, Kazushige; Sasaki, Kazuhito; Emoto, Shigenobu; Murono, Koji; Sonoda, Hirofumi; Ishihara, Soichiro
Abstract: Background: Persistent descending mesocolon (PDM) is a fetal abnormality in which the left‐sided colon is not fused to the retroperitoneum, and it is often accompanied by the adhesion between the mesocolon and small bowel mesentery. Due to its rarity, whether PDM exhibits anatomical characteristics of the inferior mesenteric artery (IMA) and left colic artery (LCA), and how the anomaly affects laparoscopic surgery are largely unknown. We investigated the branches of these arteries and outcomes of patients who underwent laparoscopic surgery. Methods: Based on computed tomography (CT) and three‐dimensional CT angiography, branching patterns of the IMA, LCA and branches originating from the LCA were analysed in 954 patients with left‐sided colon or rectal cancer. PDM was diagnosed by preoperative CT colonography, and confirmed at time of surgery. The anatomical features of the vessels and short‐term outcomes of laparoscopic surgery were compared between patient groups stratified by PDM. Results: Twelve patients (1.3%) were diagnosed with PDM. No branching pattern of the IMA specific to PDM was noted. On the other hand, patients with PDM had fewer branches (mean: 1.0) from the LCA than those without PDM (mean: 1.8, p  = 0.009). In patients undergoing laparoscopic surgery, outcomes such as operative time, intraoperative blood loss, and number of harvested nodes were comparable between the two patient groups. Conclusion: Few branches of the LCA characterize PDM. PDM does not complicate laparoscopic surgery of the left‐sided colon and rectum. However, the above anatomical feature increases the risk of poor colonic perfusion when dividing the LCA. Abstract : Anatomical features of the inferior mesenteric and left colic arteries and surgical outcomes of patients who underwent laparoscopic surgery were compared between patients with persistent descending mesocolon and those without. Fewer branches of the left colic artery were observed in those with persistent descending mesocolon. There was no significant difference in surgical outcomes between the two groups. This novel anatomical finding reveals the risk of perfusion in the proximal colon when dividing the left colic artery in such patients.